Maternal Self Efficacy in Mothers Who Have Children with Autism Spectrum Disorder (ASD) - Eliana Kurniawati; Suryanto Suryanto (Eduvest - Journal of Universal Studies, 2025)
One of the key factors supporting a mother's success in fulfilling her maternal role is maternal self-efficacy, which refers to a mother's confidence in her ability to care for her child effectively. This research examines maternal self-efficacy in mothers raising children with autism spectrum disorder (ASD). The study aims to analyze the factors influencing maternal self-efficacy in this context. A phenomenological approach was used, employing Interpretative Phenomenological Analysis (IPA). The study involved two mothers of children with ASD, with data collected through structured telephone interviews. The findings revealed that both mothers demonstrated strong maternal self-efficacy, shaped by five main factors: emotional state, appropriate parenting strategies, specialized teaching methods, provision of protection and security, and quality time spent with their children. Support from family members was also crucial in enhancing maternal confidence. Despite initial emotional difficulties, the mothers developed resilience and adaptive strategies to address their children's needs. This research highlights the importance of emotional regulation and social support in fostering maternal self-efficacy, which is essential for positive maternal and child health outcomes. The study’s insights can inform interventions aimed at empowering mothers of children with ASD, ultimately improving both parenting effectiveness and child development. Further research with more diverse participants is recommended to broaden the understanding of maternal self-efficacy in families affected by ASD. In conclusion, both participants in this study exhibited strong maternal self-efficacy in carrying out their roles as mothers.